Desenvolvimento de molho de macaúba (Acrocomia spp.): características fisico-químicas, sensoriais ecompostos bioativos - Fonseca, Jeniffer Viviany dos Santos (2020)
Sauces with macauba pulp was formulated without gum (SWG), with xanthan gum (SXG) and with gum arabic (SAG) and stored in glass and polypropylene (PP) in a refrigerator at 5 °C.Macauba pulp has 26.19% lipids, 68.76% oleic acid, 9.03% linoleic acid and 40% dietary fibers. Flavanols were predominant such as catechin, epicatechingallate, epigallocatechingal-late and procyanidin B2, contributing to the antioxidant activity. The sauces had a high fiber content (10%) and low fat content (6%), with an intense yellow color due to the carotenoid content. The sauces showed non-Newtonian behavior with stability influenced by the storage temperature. The SXG stored in PP bottles showed the highest stability (100%) for 28 days of storage at 5 ºC. SGA showed lower peroxide value in PP bottles at 5ºC and was preferred by the tasters. Macauba pulp is an alternative base ingredient for formulating sauces.